PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA PERTAMBANGAN MINERAL DAN BATU BARA YANG DILAKUKAN SECARA ILEGAL (Studi Putusan Nomor : 01/Pid.Sus./2022/PN.Tjk) - Marpaung, Lintje Anna; Rahmaddin, Nopdi Surya (Bahasa Indonesia, 2024)
Indonesia is very rich in its abundant natural resources, making mining one of the industrial ventures that can be relied upon to bring foreign exchange to the country. However, in managing these natural resources, many people misuse them, as is often reported, with an increasing number of illegal miners operating without official government permits. Several locations for non-metallic mineral and rock mining are allowed to operate without business licenses. This clearly violates legal provisions because, according to Law No. 4 of 2009 on Mineral and Coal Mining, mining operations can only be conducted if they have a Mining Business License (IUP). The issue to be discussed is whether the factors causing individuals to commit illegal mining offenses, based on the study of Decision No. 1098/Pid.Sus/2022/PN Tjk, and how criminal liability for those involved in illegal mineral and coal mining should be addressed, also based on the study of Decision No. 1098/Pid.Sus/2022/PN Tjk. The research method used is normative juridical and empirical approaches, utilizing secondary and primary data obtained from literature studies and field studies, with data analysis conducted through normative juridical analysis.